KONSUMSI BERAS TINGKAT RUMAH TANGGA DI DAERAH ISTIMEWA YOGYAKARTA - , FISKA RAHMAWATI SANTOSO, Bapak Prof. Dr. Ir. Dwidjono HD, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to: 1) determine factors that influenced the level of household consumption of rice, 2) determine the elasticity of demand for rice at the household level, and 3) determine differences of household rice consumption in rural and urban areas. This study used National Socio-Economic Survey (SUSENAS) data at household level from Central Bureau of Statistic (BPS) in 2011 for Yogyakarta Special Region. About 173 households out of 3200 households in rural and urban areas were chosen as sample in this research. The first and second objectives were analyzed by using OLS method, while the third objective was analyzed by using t-test. The results showed that householdsâ rice consumption was influenced by the prices of rice, sweet potato, instant noodles, beef, tempe, number of household members, income, and location of residence. Household consumption of rice in Yogyakarta was positively influenced by the price of instant noodles and the number of household members, but it was negatively affected by the price of rice, beef prices, and income. There was a difference between rice consumption in urban and rural areas. Based on the concept of price elasticity, it was known that householdsâ rice consumption was inelastic, instant noodles is substitutes of rice, and beef was complementing rice. The average household rice consumption in rural areas was higher than that of urban households.